Foreign aid and sustainable fisheries management in sub-Saharan Africa - Wisdom Akpalu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The fisheries sector in sub-Saharan Africa has benefitted from high and increasing amounts of foreign aid for over four decades. In the 1990s when evidence emerged that most stocks were overcapitalized and overfished, the effectiveness of fisheries development aid, particularly those directed at fishing capacity enhancement, came into question. This report examined the relationship between development aid and capture fisheries management in sub-Saharan Africa and found that, indeed, capacity enhancing subsidies can explain losses in the fisheries sector. Furthermore, we have argued that assigning and protecting fishing rights may not be sufficient to generate first best outcomes in practice. Development aid should, in addition to building fisheries institutions, be directed at fisheries research and development, tied to good governance, as well as be directed at protecting fish stocks.
Keywords: F35; O55; Q22; 330; development aid; fisheries management; sub-Saharan Africa